First record of the Indo-Pacific humpback dolphins (Sousa chinensis) southwest of Hainan Island, China. Issue 1 (December 2016) - Li, Songhai; Lin, Mingli; Xu, Xiao; Xing, Luru; Zhang, Peijun; Gozlan, Rodolphe; Huang, Shiang-Lin; Wang, Ding
Abstract Background Populations of Indo-Pacific humpback dolphins (Sousa chinensis ) in China were known to be distributed from the Beibu Gulf near the border with Vietnam to the mouth of the Yangtze River. According to existing studies, the waters around Hainan Island, China, were not considered to be part of the humpback dolphins' distribution. Results In 2014, for the first time, we recorded humpback dolphins in waters southwest of Hainan Island. Conclusions This record expands the known southern distribution range of this dolphin in Chinese waters by more than 300 km.